Caracterização da vegetação e da entomofauna de solo de fragmentos de floresta estacional semidecidual no sul de Goiás - Soares, Narcisa Silva (2012)
The agriculture expansion over native vegetation has provocaded habitat fragmentation in main Brazilian biomes. It was described the vegetation and the entomofauna of four semi deciduous forest fragments, which represent remnants of the Atlantic Rainforest, inserted in the Cerrado domain, as well as the abundance and the body size and symmetry of the ant Pachycondyla cf. crassinoda (Ponerinae) in these fragments. The study area is located at the Itumbiara, state of Goias, Brazil, situated in the Paranaíba river valley. This area has intensive agricultural activity that has been accelerating the deforestation of natural process. The following hypotheses were tested: 1) the remnants that are geographically closer tend to be floristically more similar and the fragment size is directly related to its biological diversity, 2) fragment size and floristic composition influence the entomofauna community structure in terms of richness and abundance, 3) the fragment size affects the abundance and the fluctuating asymmetry (FA) population levels of a formicinae population and the size of their individuals. It was also investigated in this ant population whether there are correlations between body s size and symmetry with the individual s abundance and the climatic conditions. The floristic composition, the body s size and FA of Pachycondyla cf. crassinoda were influenced by the fragment size. Smaller fragments were floristically more similar to each other, despite not being geographically close and the entomofauna similarity between fragments was independent of the fragment size. The vegetation diversity did not linearly interfered with the insects abundance, but the rainfall significantly affected the density, the size and the FA of P. cf. crassinoda. All studied forest remnants are important for conservation of the local biological diversity, regardless of their size. The evaluation of forest fragmentation impact should considered a combination of several factors such as the size of the area, the surrounding matrix, the degree of isolation and the local biotic and abiotic factors.